Calculation of electronic and optical properties of 1550 nm VCSEL based on Group IV elements. (26th January 2021) - Li, Hongqiang; Zhang, Sai; Zhang, Yikai; Ding, Mingjun; Lu, Xinyan; Daniel Prades, Joan
Abstract: Si/SiGe quantum well (QW) structures show considerable potential in revolutionising Si photonics. This study proposes a novel 1550 nm vertical cavity surface-emitting laser (VCSEL) that is based on Group IV elements and composed of Si/SiO2 distributed Bragg reflectors and Si/Si0.13 Ge0.87 QWs. Material composition and QW width in the active region are optimised. The proposed Group IV-based VCSEL can exhibit epitaxial growth on a vertical binary blazed grating coupler and increase coupling efficiency relative to the traditional Group III–V-based VCSEL with an Si waveguide. The proposed VCSEL on Si based on the Group IV element scheme is a cheap, high-yielding and temperature-insensitive on-chip light source that can be used in large-scale, high-density monolithic integration.